Urgensi Penafsiran Saintifik Al-Qur’an: Tinjauan atas Pemikiran Zaghlul Raghib Muhammad al-Najjar - Intan Pratiwi Mustikasari (Universitas Darussalam Gontor, 2021)
This article aims to elaborate the views Zaghlul Raghib Muhammad An-Najjar on the urgency of scientific interpretation of the Qur'an in order to preach the spread of Islam in the modern era. This becomes attractive because in the midst of the pro and contra of tafsir ilmy among the opinions of scholars and mufassir,. Al-Najjar seeks to corroborate the evidence of the urgency of scientific interpretation in his book